2013
DOI: 10.1037/a0032164
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with child custody evaluators’ recommendations in cases of intimate partner violence.

Abstract: Although child custody evaluations can lead to unsafe outcomes in cases of intimate partner violence (IPV), little is known about factors associated with evaluators' recommendations. In this study of 465 child custody evaluators, we investigated the association between evaluators' beliefs, background, and knowledge and their custody and visitation recommendations in cases involving IPV. We hypothesized that evaluators' belief in false allegations by the mother and their recommendations that perpetrators have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…One survey conducted on community members indicated that 54% of respondents believed that claims of domestic violence are often fabricated or exaggerated to improve the outcome of custody disputes (VicHealth, 2013). Even custody evaluators are suspicious that claims of domestic violence are false (LaFortune & Carpenter, 1998; Saunders, Tolman, & Faller, 2013). The veracity of asylum seekers recalling a repeated experience is also likely to be questioned.…”
Section: Introductionmentioning
confidence: 99%
“…One survey conducted on community members indicated that 54% of respondents believed that claims of domestic violence are often fabricated or exaggerated to improve the outcome of custody disputes (VicHealth, 2013). Even custody evaluators are suspicious that claims of domestic violence are false (LaFortune & Carpenter, 1998; Saunders, Tolman, & Faller, 2013). The veracity of asylum seekers recalling a repeated experience is also likely to be questioned.…”
Section: Introductionmentioning
confidence: 99%
“…One item asked about the belief that domestic abuse reports tend to be false. Such perceptions are correlated strongly with sexist beliefs and with recommendations that place IPV victims at risk of continued abuse in child custody determinations (Saunders et al, 2013). Respondents were asked "What percentage of official domestic violence reports do you believe are false?"…”
Section: Methodsmentioning
confidence: 99%
“…Using irrelevant (Saunders, Tolman, & Faller, 2013) or value-based (Sagi & Dvir, 1993) information is particularly tempting, because the courts cannot simply rule to not rule. Using irrelevant (Saunders, Tolman, & Faller, 2013) or value-based (Sagi & Dvir, 1993) information is particularly tempting, because the courts cannot simply rule to not rule.…”
Section: Decision-making In Custody Disputes and Splitting Hairsmentioning
confidence: 99%
“…When both parents are fit, there is a risk that court decisions will be based on information or circumstances that are irrelevant or questionable from the child's point of view. Using irrelevant (Saunders, Tolman, & Faller, 2013) or value-based (Sagi & Dvir, 1993) information is particularly tempting, because the courts cannot simply rule to not rule. Hence, there may be confusion between the different goals of ensuring the child's future well-being and resolving the legal case.…”
Section: Decision-making In Custody Disputes and Splitting Hairsmentioning
confidence: 99%